AI IN HEALTHCARE: USING CUTTING-EDGE TECHNOLOGIES TO REVOLUTIONIZE VACCINE DEVELOPMENT AND DISTRIBUTION - Nasrullah Abbasi; Nizamullah FNU; Shah Zeb (JURIHUM : Jurnal Inovasi dan Humaniora, 2023)
The field of vaccine development is being revolutionized by artificial intelligence (AI), which is bringing revolutionary advancements to every stage of the process from discovery to dissemination. This review focuses on a few important aspects as it examines how AI technology improve vaccine development procedures. By locating antigen targets, forecasting immune responses, and refining vaccine designs via sophisticated machine learning and computational biology, artificial intelligence (AI) expedites the search for new vaccines. Artificial Intelligence (AI) enhances clinical trial efficacy by facilitating real-time data monitoring, optimizing trial designs, and improving participant recruitment. AI improves quality control, predictive maintenance, and process efficiency in the production of vaccines, resulting in constant and dependable output. AI also facilitates timely and equitable vaccination delivery by optimizing cold chain management, transportation logistics, and supply chain management. Despite these developments, there are still issues with data integration and quality, model transparency, ethical and legal issues, and computational resource requirements when using AI in vaccine development. Prospective avenues for investigation comprise investigating tailored vaccinations, improving real-time monitoring, and advocating for worldwide health parity. Leveraging AI's full potential to advance vaccine research will require addressing these issues and seeking creative solutions. Improvements in health outcomes and more efficient responses to risks to global health will result from the ongoing cooperation of AI specialists, vaccine developers, and public health agencies.